Your body, your voice : the key to natural singing and speaking - Dimon, Theodore, Jr (North Atlantic Books, 2011)
"Your Body, Your Voice presents the basic underlying design principles of the human voice, addresses harmful patterns of speech and singing, and offers techniques designed to restore the voice to its full potential"--Provided by publisher.